STRATEGI FKUB BANDAR LAMPUNG DALAM MENUMBUHKAN TOLERANSI UMAT BERAGAMA - Idrus Ruslan Idrus; Sonhaji Sonhaji (Harmoni, 2021)
The focus of the this research is to examine the duties and responsibilities of FKUB in realizing a tolerant life as a capital for community resilience. The basic thing is that Indonesia is a diverse country, as well as the conditions in the city of Bandar Lampung. Therefore, FKUB in this city has a strategy in foresting tolerance between religious communities. The theory used is the theory of symbolic interactionism with the character John Dewey and C.H. Cooley, as well as the deconfessionalization theory proposed by C.A.O. Van Niuwenhuijz. This research is a type of field research which is descriptive with qualitative analysis. Data collection techniques by means of observation, interviews and documentation. The results showed that the strategy carried out by the Bandar Lampung FKUB in fostering interfaith tolerance was in addition to being based on the main task, also making youth (adolescents and students) the targets of the work program because they would later become leaders. The supporting factors are the solidity of the management, financial support from the Government, and the participation of the religious community. While the inhibiting factors come from internal as well as external. Internal factors where the management has their own busyness, while external inhibiting factors include the conflict of interest between the FKUB and the Regional Government, this happens because of different points of view in seeing an activity.